FROM LEX TO IUS: REORIENTING INDONESIAN LEGAL REFORM TOWARD INSTITUTIONALISATION AND SOCIAL LEGITIMACY - Ilham Yuli Isdiyanto; Retno Saraswati; Ratna Herawati (Doctoral of Law Program, Faculty of Law, Universitas Diponegoro, 2026)
This study examines the tension between institutionalised law and coercive law within Indonesia’s national legal system. It addresses the persistent divide between formally valid rules and socially legitimate norms in a plural legal order shaped by state law, customary law, religious law, and colonial legal legacies. Employing a doctrinal and conceptual methodology, supported by socio-legal, philosophical, hermeneutic, critical, and comparative approaches, the study analyses legislation, judicial principles, legal theory, and Indonesia’s legal experience. The findings indicate that excessive reliance on coercion produces only superficial compliance while generating institutional distrust, legal alienation, selective enforcement, and social resistance. Conversely, law that is internalised by society is more likely to secure enduring legitimacy and voluntary obedience. Indonesia’s legal crisis, therefore, does not primarily arise from a shortage of legal rules, but from a failure of institutionalisation caused by the disconnection between formal law, living law, and public values. The study also identifies an emerging legislative shift towards mediation, restorative justice, alternative dispute resolution, and community-based settlement, including reforms introduced through the 2023 Criminal Code and the 2025 Criminal Procedure Code. Nevertheless, these developments remain vulnerable to formalistic implementation and an entrenched coercive institutional culture. This study argues that authentic legal institutionalisation requires a transition from a lex-centred paradigm to an ius-oriented legal order grounded in Pancasila, legal pluralism, procedural justice, meaningful public participation, and progressive legal thought. Accordingly, legal reform must extend beyond statutory amendment to encompass legal education, institutional culture, access to justice, recognition of customary law, and restorative mechanisms. The study contributes a conceptual framework in which Indonesian legal legitimacy is understood as the product of internalisation, social recognition, institutional responsiveness, and democratic participation, rather than coercive authority alone. This framework offers a normative basis for assessing whether legal institutions command genuine public acceptance and sustain justice in practice over time.